Pemahaman Mahasiswa terhadap Kondisi Manajemen Pengetahuan dan Manajemen Inovasi PTS DKI Jakarta - Dyah Budiastuti (Bina Nusantara University, 2013)
Private university (PTS) is a business that is based on knowledge; and relies on innovation in efforts to achieve the performance and competitive advantages. As a result, the implementation of knowledge management and innovation management becomes very important. This research aims to determine students' understanding of the condition of knowledge and innovation management and its influence on the achievement of performance in 5 private universities in region III Kopertis Jakarta with the most number of active students. Data were analyzed using descriptive statistics. The results showed that the condition of knowledge management is able to create the value, and the condition of innovation management has enough value-added for stakeholders.